Hyperprogressive disease in hepatocellular carcinoma with immune checkpoint inhibitor use: a case series. (16th January 2019) - Wong, Daniel Jiahao; Lee, Joycelyn; Choo, Su Pin; Thng, Choon Hua; Hennedige, Tiffany
Immune checkpoint inhibitors (ICIs) have demonstrated promising results in a variety of advanced cancer types. The phenomenon of hyperprogressive disease (HPD) has only been documented in recent years, however, there have been no reports of HPD in hepatocellular carcinoma. We present a case series of six patients with advanced hepatocellular carcinoma treated with ICIs who demonstrated rapid radiological progression, this was confirmed by comparing tumor growth rates before and during treatment with HPD defined as tumor growth rateratio ≥2. Although ICIs have demonstrated profound efficacy in advanced cancer, they might also be responsible for HPD in a small subset of patients. The ability to predict treatment response to ICI is thus of importance in protecting patients from the deleterious effects of HPD.